ABOUT SOME POSSIBILITIES OF USING THE INTERNATIONAL OF THINGS IN THE EDUCATIONAL SPHERE - A. P. Preobrazhenskiy (Science and Innovation Center Publishing House, 2020)
In this paper, we consider the possibilities of using Internet of things technologies in the educational sphere. Examples of increasing the effectiveness of training are given.